2022
DOI: 10.1007/s13197-022-05580-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of herbal extracts and supplement mixture on alcohol metabolism in Sprague Dawley-rats

Abstract: This study aimed to investigate the effect of mixture of herbal extracts and supplementary formula (FNP-C) on hangovers and antioxidant enzymes in alcohol-induced liver damage in rats. HepG2 cells were used as the experimental cells and divided into five groups: non-treated control (normal), alcohol-induced control (control), mixture of herbal extracts (FNP-B), FNP-C, and a commercial treatment of liver diseases (Livers®); inhibition of detoxification and alcohol-induced damage was confirmed in vivo. Blood alc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Recently, many people have shown interest in natural plants and drinks that treat hangovers owing to an increase in income and quality of life [ 6 ]. Moreover, research is being conducted to identify liver-protective substances derived from natural products that are safe and have excellent antioxidant activity [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, many people have shown interest in natural plants and drinks that treat hangovers owing to an increase in income and quality of life [ 6 ]. Moreover, research is being conducted to identify liver-protective substances derived from natural products that are safe and have excellent antioxidant activity [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Because many people experience hangover, 10,11 hangover products derived from natural substances could be an effective strategy for relieving hangover symptoms because they have abundant antioxidants. 12 A previous study reported that many plants, fruits, and vegetables, such as Pueraria Lobata, Fructus Evodiae, Trigonela Foenum-Graecum, Hovenia Dulcis, Pyrus Pyrifolia, Mangifera Indica L., Diospyros Kaki Thunb., Thymus Vulgaris, Zingiber Officinale, Asparagus Officinalis, Oenanthe Javanica, Opuntia Ficus-Indica, and Panax Ginseng, have alcohol clearance effects by upregulating ADH and ALDH activity. 13 Noni (Morinda citrifolia L.) is a plant belonging to the Rubiaceae family and is also known as beach mulberry or cheese fruit.…”
Section: Introductionmentioning
confidence: 99%
“…5 Acetaldehyde, an intermediate metabolite, possesses high reactivity and exerts significant hepatotoxicity; its accumulation within the body can result in severe hangover symptoms. [34][35][36] Therefore, eliminating acetaldehyde can effectively alleviate alcohol-induced hangovers and mitigate liver toxicity. For instance, Tiaogan Jiejiu Tongluo Formula, by lowering the activity of ADH and raising the activity of ALDH, accelerates the conversion of acetaldehyde to acetic acid, alleviates the accumulation of large amounts of acetaldehyde and chronic acetaldehyde poisoning, and reduces the chronic liver injury induced by alcohol in SD rats.…”
mentioning
confidence: 99%